Gift exchange and workers' fairness concerns: when equality is unfair - Johannes Abeler; Steffen Altmann; Sebastian Kube; Matthias Wibral (Institute for the Study of Labor (IZA), 2009)
We study how different payment modes influence the effectiveness of gift exchange as a contract enforcement device. In particular, we analyze how horizontal fairness concerns affect performance and efficiency in an environment characterized by contractual incompleteness. In our experiment, one principal is matched with two agents. The principal pays equal wages in one treatment and can set individual wages in the other. We find that the use of equal wages elicits substantially lower efforts. This is not caused by monetary incentives per se since under both wage schemes it is profit-maximizing for agents to exert high efforts. The treatment difference instead seems to be driven by the fact that the norm of equity is violated far more frequently in the equal wage treatment. After having suffered from violations of the equity principle, agents withdraw effort. These findings hold even after controlling for the role of intentions, as we show in a third treatment. Our results suggest that adherence to the norm of equity is a necessary prerequisite for successful establishment of gift-exchange relations.
urn:nbn:de:101:1-20090720381
Keywords: J33; D63; M52; C92; J41; 330; Wage setting; wage equality; equity; gift exchange; reciprocity; incomplete contracts; Arbeitsbeziehungen; Lohnverhandlungen; Gerechtigkeit; Ökonomischer Anreiz; Unvollständiger Vertrag; Agency Theory